The Competing-risk analysis of post-IPO delistings - Chen, J (New Zealand Finance Colloquium, 2011)
This paper is working on one IPO panel data to estimate the predicting power of some covariates on future status of IPO firms after going public. Specifically, our study aims to study how the possibility of the delisting due to different reasons, including merges, moves between exchanges, and bad performance (liquidation/Bankruptcy), is affected by those covariates. The results show that the inclusion of the aftermarket performance in a competing risk model helps to distinguish the impact of those covariates on the delistings caused by three events. There are three main results from our analysis. First, it is found that most of covariates have significant effects on two types of delistings, mergers- and failure-originated. On the other side, only firm size and capital structure are related to the delisting when the IPO firm switches to another exchange. Second, we find that some covariates have significant effects on two delistings, acquisition/merger- or liquidation/bankruptcy-originated, in the same direction, including technology dummy, IPO activity, firm age, asset growth, R&D expenses, and leverage. Third, three covariates, including venture capital dummy, profitability, and firm size, have opposite effect on different events triggering the delisting, mergers and bad performance. The increase of these covariates could increase the risk of acquisition/merge delisting whereas reduce the risk of failure delisting.